Human metabolic phenotype diversity and its association with diet and blood pressure - Holmes, Elaine; Loo, Ruey Leng; Stamler, Jeremiah; Bictash, Magda; Yap, Ivan K. S.; Chan, Queenie; Ebbels, Tim; De Iorio, Maria; Brown, Ian J.; Veselkov, Kirill A.; Daviglus, Martha L.; Kesteloot, Hugo; et al. (Nature, 2008)
Metabolic profiling: Broad-brush epidemiology Metabolic profiling — the analysis of the relative levels of many different metabolites in blood or urine — can reveal a lot about how diet and lifestyle contribute to risks for certain diseases. Profiling of urine samples from more than 4,000 individuals taking part in the INTERMAP epidemiological study demonstrates significant differences in metabolism both from country to country and within populations. Metabolites discriminating across populations were linked to data on blood pressure, a major risk factor for coronary heart disease and stroke. Formate, alanine and hippurate excretion emerged as markers related to blood pressure. Overall the data show that lifestyle is a dominant feature in determining metabolism. This work lays the foundation for a 'metabolome-wide association' approach to molecular epidemiology. This paper presents a large scale, multi-national population-based urinary metabolic profiling analysis from individuals participating in the InterMap study. Metabolic phenotypes are the products of interactions among a variety of factors—dietary, other lifestyle/environmental, gut microbial and genetic 1 , 2 , 3 . We use a large-scale exploratory analytical approach to investigate metabolic phenotype variation across and within four human populations, based on 1 H NMR spectroscopy. Metabolites discriminating across populations are then linked to data for individuals on blood pressure, a major risk factor for coronary heart disease and stroke (leading causes of mortality worldwide 4 ). We analyse spectra from two 24-hour urine specimens for each of 4,630 participants from the INTERMAP epidemiological study 5 , involving 17 population samples aged 40–59 in China, Japan, UK and USA. We show that urinary metabolite excretion patterns for East Asian and western population samples, with contrasting diets, diet-related major risk factors, and coronary heart disease/stroke rates, are significantly differentiated ( P < 10 -16 ), as are Chinese/Japanese metabolic phenotypes, and subgroups with differences in dietary vegetable/animal protein and blood pressure 6 . Among discriminatory metabolites, we quantify four and show association ( P < 0.05 to P < 0.0001) of mean 24-hour urinary formate excretion with blood pressure in multiple regression analyses for individuals. Mean 24-hour urinary excretion of alanine (direct) and hippurate (inverse), reflecting diet and gut microbial activities 2 , 7 , are also associated with blood pressure of individuals. Metabolic phenotyping applied to high-quality epidemiological data offers the potential to develop an area of aetiopathogenetic knowledge involving discovery of novel biomarkers related to cardiovascular disease risk.